Novel Nuclear Import of Vpr Promoted by Importin α Is Crucial for Human Immunodeficiency Virus Type 1 Replication in Macrophages - Nitahara-Kasahara, Yuko (American Society for Microbiology, 2007)
Monocytes/macrophages are major targets of human immunodeficiency virus type 1 (HIV-1) infection. The viral preintegration complex (PIC) of HIV-1 enters the nuclei of monocyte-derived macrophages, but very little PIC migrates into the nuclei of immature monocytes. Vpr, one of the accessory gene products of HIV-1, is essential for the nuclear import of PIC in these cells, although the role of Vpr in the entry mechanism of PIC remains to be clarified. We have shown previously that Vpr is targeted to the nuclear envelope and then transported into the nucleus by importin α alone, in an importin β-independent manner. Here we demonstrate that the nuclear import of Vpr is strongly promoted by the addition of cytoplasmic extract from macrophages but not of that from monocytes and that the nuclear import activity is lost with immunodepletion of importin α from the cytoplasmic extract. Immunoblot analysis and real-time PCR demonstrate that immature monocytes express importin α at low levels, whereas the expression of three major importin α isoforms markedly increases upon their differentiation into macrophages, indicating that the expression of importin α is required for nuclear import of Vpr. Furthermore, interaction between importin α and the N-terminal α-helical domain of Vpr is indispensable, not only for the nuclear import of Vpr but also for HIV-1 replication in macrophages. This study suggests the possibility that the binding of Vpr to importin α, preceding a novel nuclear import process, is a potential target for therapeutic intervention.